Study on Prevalence of Bovine Cysticercosis and Human Taeniasis in Jigjiga Town, Somali Region, Eastern Ethiopia (Global Journal of Medical Research, 2021)
A cross-sectional study was conducted from November 2019 to April 2020 on bovine slaughtered in Jigjiga municipal abattoir to determine the prevalence, cyst viability, organ distribution, and public health significance of bovine cysticercosis. Among 340 examined cattle, 11(3.24%) were found to be infected by Cysticercus bovis. The comparative higher prevalence was observed in female animals (3.4%) than male (2.9%) but a significant difference was not observed. Age-wise prevalence result showed that significantly (p
Keywords: bovine; cysticercosis; cyst viability; jigjiga; organ; prevalence; public health